BRAND STRATEGY IN THE HIGH-END SEGMENT: THE INFLUENCE OF COLOR PSYCHOLOGY ON CONSUMER WILLINGNESS TO PAY (American Journal of Interdisciplinary Research and Development, 2026)
This article comprehensively analyzes the impact of color perception on consumer willingness to pay in the high-end segment. The research is based on theories from consumer psychology, neuromarketing, and brand management that suggest that color contributes to price-related decisions through emotional reactions, quality perception, and symbolic capital formation. The cognitive and affective effects of colors, their dependence on the cultural context, as well as their role in the visual strategy of luxury brands are considered. In the High-end segment, color acts as a price signal and status indicator, rather than just an aesthetic element. Black, gold, dark blue and metallic shades increase the consumer's psychological willingness to pay higher prices, determining the exclusivity, quality and reputation of the product. The article will analyze the theory of symbolic capital, sensory marketing and brand identity, as well as show the strategic importance of color management. The results of the study prove that the color policy for high-end brands is closely related to the pricing strategy. In future research, it is recommended to pay special attention to cross-cultural features and the role of visual perception in the digital environment.